Reshaping Croatian National Identity - Changing concept of the heritage presentation and museums practice - Babić, Darko (Array, 2006)
In Croatia, we have the National Library and the National Archive, but do not have a National Museum. Furthermore, in the first five to six years of its recent independence, Croatia has seen a decrease in the number of general museums. Post-war museum activity called for a rethinking of mission and practice, and a search for lost visitors. The University of Zagreb’ s museological expertise has been used to again reinvent the museum, not least as a medium of national or regional identity. The first part of this changing concept of the museum has been new communications through collections, and new organisations such as that responsible for The Ecopark Pernat at the Island of Cres. New museums have also resulted including the House of Batana. A Batana is a small fishing boat which here becomes symbolic of community identity.